PENGEMBANGAN KOMPETENSI DIGITAL GURU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR DALAM KERANGKA KURIKULUM MERDEKA - Maimunatun Habibah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
The use of various new technologies in the learning process has strengthened since the COVID-19 pandemic. The practice has two general implications, positive and negative. This paper seeks to reveal the efforts of Islamic religious education teachers at the elementary school level in increasing their digital competence amid the strengthening of new technology in learning. This study used descriptive qualitative research methods. This study indicates that the development of digital teacher competencies takes place through two stages—First, the stage of strengthening digital competence by following technical guidance on the management and use of ICT for elementary school (SD, Sekolah Dasar) teachers, developing it by self-study through the use of YouTube, making products in the form of Google Sites, and using it in the learning process in the classroom. Second, implementing a post-guidance training program for teachers and students at the school where they work. The study’s implications are discussed within the framework of an independent curriculum. The practical suggestion of this study lies in the importance of integrating technical guidance, teacher’s independent learning, and collaboration between teachers as the basis for developing teacher competence.